Draft of the Diocesan Program for Awakening Priestly Vocations. Basics and Proposals (Including American) - Bartoszek, Antoni (Studia Warmińskie, 2024)
This article presents a draft of an inter-diocesan program designed to awake priestly vocations. The author presents the draft in the context of a radical decline in the number of candidates for the sacrament of Holy Orders and the prospect of parish mergers and even church closures. The present considerations are not limited to presenting pastoral techniques to encourage young people to open their hearts to God's call. Above all else they present the importance of rediscovering the beauty and value of the two related sacraments: Eucharist and the ministerial priesthood. Deep theological analysis of these sacraments as well as spiritual reflection on them can contribute to enthusiasm of the community of believers regarding concern for priestly vocations. This enthusiasm can lead to a new commitment of the diocesan priestly community, parish communities and their families, as well as the sick offering their sufferings for vocations. These engagements, translated into concrete pastoral initiatives (drawn from the Polish and American experience to date), may open the hearts of young people to accept the gift of the priestly vocation. The most important conclusion of the present analyses is: concern for vocations is an activity with the following characteristics: it is broad, i.e., interdiocesan; it is long-term, i.e., designed for many years; and, above all, it is deepened, i.e., built on the theology of the sacraments instituted in the Upper Room at the Last Supper by the Lord Jesus.